Let's fill in the steps to complete the square for the equation \( x^2 + 12x - 14 = 0 \).
-
Start with the equation: \[ x^2 + 12x - 14 = 0 \]
-
Move the constant term to the other side: \[ x^2 + 12x = 14 \]
-
Complete the square by adding and subtracting the square of half the coefficient of \(x\): \[ x^2 + 12x + 36 = 14 + 36 \]
-
The \( 36 \) is obtained by taking half of \( 12 \) (which is \( 6 \)) and squaring it (\( 6^2 = 36 \)).
-
Now we simplify: \[ (x + 6)^2 = 50 \]
-
At this point, we need to take the square root of both sides: \[ x + 6 = \pm \sqrt{50} \]
-
This can be simplified further: \[ x + 6 = \pm 5\sqrt{2} \]
-
Now we isolate the variable by subtracting \( 6 \) from both sides: \[ x = -6 \pm 5\sqrt{2} \]
Final answers are: \[ x = -6 + 5\sqrt{2} \quad \text{and} \quad x = -6 - 5\sqrt{2} \]
So, let's summarize the filled areas:
- x² + 12x + 36 = 14 + 36
- (x + 6)² = 50
- Take the square root of both sides
- x = -6 ± 5√2